A cataluminescence gas sensor based on mesoporous Mg-doped SnO2 structures for detection of gaseous acetone. Issue 43 (25th October 2016) - Weng, Yueyang; Deng, Dongyan; Zhang, Lichun; Su, Yingying; Lv, Yi
Abstract : In this paper, Mg-doped SnO2 materials were synthesized through a simple environmentally friendly hydrothermal method showing a remarkable cataluminescence activity for acetone detection. Abstract : In this work, the fabrication of mesoporous magnesium doped tin oxide (Mg-doped SnO2 ) materials with various doping levels has been achieved through a facile one pot and low cost hydrothermal method without the use of a surfactant. The structure, morphology, chemical states and specific surface area were analyzed in detail. By tuning the amount of Mg doping concentration, a series of Mg-doped SnO2 structures with various morphologies including flower-shaped, nanopolyhedrons, nanocubes, and microcubes were successfully synthesized. It was found that the concentration of the Mg dopant has a significant effect on the crystal structure, surface area and morphology. Moreover, the 1 : 3 Mg-doped SnO2 had a specific surface area as high as 138.6 m 2 g −1 with a pore size of ca. 3.8 nm. The as-synthesized Mg-doped SnO2 materials and commercial SnO2 powders were used to fabricate cataluminescence gas sensor devices for acetone. It was noted that the CTL sensor based on 1 : 3 Mg-doped SnO2 nanomaterials displayed excellent acetone gas sensing performances such as a fast response time (2 s)/recovery time (25 s), high sensitivity, and good repeatability and selectivity, which indicated that 1 : 3 Mg-doped SnO2 materials would have very promising applications in high performance acetone sensors.